A case study on the vertical distribution and characteristics of aerosols using ground-based raman lidar, satellite and model over Western India. Issue 17 (2nd September 2021) - Saha, Sourita; Sharma, Som; Kumar, K. Niranjan; Kumar, Prashant; Joshi, Vaidehi; Georgoussis, George; Lal, S.
ABSTRACT: Ahmedabad is an urban site in western region of India. Dust loading and its variability are very high over this semi-arid location. A state-of-the-art ground-based Raman lidar has been used for the study of day-to-day variability in vertical distribution of aerosol loading over Ahmedabad (23.02° N, 72.57° E) from 8 to 11 May 2018. We have done a comprehensive study about vertical profiles of aerosols across two wavelengths recorded simultaneously, namely, 355 nm and 532 nm, over this location. An interesting hump feature has been noted on 9 May at around 18 h (Local Time), with an additional peak at 19 h on 10 May. The loading over this region has more fine-mode aerosols than coarse-mode particles. Further, findings from ground-based lidar have been compared with MACC-II model simulations and Cloud-Aerosol Lidar with Orthogonal Polarization on-board Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observational. Back-trajectory analysis showed majority of the influx came from middle-east, carrying mineral dust and traces of marine aerosols from Arabian Sea, except for 11 May, where low-level dust carrying trajectories and also coarser dust particles were not seen. This type of manifestation has also been observed while classifying aerosols over Ahmedabad using Lidar Depolarization Ratio and Lidar Ratio obtained from Raman Lidar. Fine mode aerosols have been characterized as industrial, vehicular and marine, while coarser as mineral dust and biomass burning. This study focuses on local variation and classification of aerosols based on size and type, which will further help in better estimation of radiative budget and other impacts of aerosols.